2018
DOI: 10.1038/s41409-018-0264-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of hematopoietic stem cell transplantation for the treatment of multiple myeloma: a Mayo Stratification of Myeloma and Risk-Adapted Therapy (mSMART) consensus statement

Abstract: Over the last two decades, the utilization of various novel therapies in the upfront or salvage settings has continued to improve survival outcomes for patients with Multiple Myeloma (MM). Thus, the conventional role for hematopoietic stem cell transplantation (HSCT) in MM either in the form of an autologous stem cell transplant (ASCT) or an allogeneic stem cell transplant (Allo-SCT) warrants re-evaluation, given the aforementioned clinical advances. Here, we present a consensus statement of our multidisciplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 142 publications
(114 reference statements)
0
75
0
4
Order By: Relevance
“…Definitions of therapeutic approaches within this paradigm of long-term treatment are summarized in Table 1 4,5 . This paradigm is being increasingly followed, with safety profiles of newer drugs improving long-term treatment feasibility vs. older agents 2 . Various long-term approaches in newly diagnosed MM (NDMM) are discussed within current guidelines and recommendations 1,[6][7][8][9][10] . Consequently, and associated with benefits demonstrated in randomized clinical trials, long-term therapy is used extensively in routine clinical practice in some geographies.…”
Section: Introductionmentioning
confidence: 99%
“…Definitions of therapeutic approaches within this paradigm of long-term treatment are summarized in Table 1 4,5 . This paradigm is being increasingly followed, with safety profiles of newer drugs improving long-term treatment feasibility vs. older agents 2 . Various long-term approaches in newly diagnosed MM (NDMM) are discussed within current guidelines and recommendations 1,[6][7][8][9][10] . Consequently, and associated with benefits demonstrated in randomized clinical trials, long-term therapy is used extensively in routine clinical practice in some geographies.…”
Section: Introductionmentioning
confidence: 99%
“…Low-risk patients derived the largest benefit [40]. Retrospective studies have also confirmed the efficacy and safety of salvage ASCT [41]. Furthermore, salvage ASCT may restore the integrity and function of the bone marrow and compensate for drug-related hematological toxicity [42].…”
Section: Salvage Repeating Of Asctmentioning
confidence: 93%
“…Taking into consideration that NDMM patients who achieved MRD negativity in the IFM 2009 trial showed similar OS rates irrespective of the administration of upfront ASCT [16], MRD status with salvage re-induction may guide the decision for proceeding to a salvage ASCT. Therefore, salvage ASCT should be considered among patients who have been in remission after the initial ASCT for at least 36 or 18 months with or without maintenance, respectively [41], especially those with favorable disease characteristics.…”
Section: Salvage Repeating Of Asctmentioning
confidence: 99%
“…At the same time, the concept of "double-hit" and "triple-hit" was proposed (defined as that: 2 or even 3 high-risk genetic abnormalities existence the same time.) [10,11]. Also, amount of clinic trials had confirmed its prognostic outcomes.…”
Section: Ivyspring International Publishermentioning
confidence: 94%